THE EFFECT OF INTENSIVE READING ON VOCABULARY MASTERY OF SMAN 2 TAPUNG STUDENTS - Rifka Hosianna Hutabarat; Supriusman Supriusman; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aimed at finding out whether there is the effect of intensive reading on vocabulary mastery of SMAN 2 Tapung Students. This research used a sequential explanatory mixed method combining quantitative and qualitative methods. The sample of this research is 30 students of XI IPS 1 class. The research data were collected through Pre-test and Post-test as the research instrument. The test items consist of synonyms and antonyms. The result revealed that the posttest mean score was higher than the mean score of the pretest. Additionally, the result of hypothesis analysis showed that the significance 2-tailed was lower than the alpha that was 0.000 ≤ 0.050. It indicated that Ho (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. Briefly, in all the explanations above there was a significant effect of intensive reading on vocabulary mastery of SMAN 2 Tapung Students.Key Words: Intensive Reading and Vocabulary Mastery